The Zinc Transporter Zip5 (Slc39a5) Regulates Intestinal Zinc Excretion and Protects the Pancreas against Zinc Toxicity - Geiser, Jim; De Lisle, Robert C.; Andrews, Glen K. (PLOS ONE, 2013)
Background ZIP5 localizes to the baso-lateral membranes of intestinal enterocytes and pancreatic acinar cells and is internalized and degraded coordinately in these cell-types during periods of dietary zinc deficiency. These cell-types are thought to control zinc excretion from the body. The baso-lateral localization and zinc-regulation of ZIP5 in these cells are unique among the 14 members of the Slc39a family and suggest that ZIP5 plays a role in zinc excretion. Methods/Principal Findings We created mice with floxed Zip5 genes and deleted this gene in the entire mouse or specifically in enterocytes or acinar cells and then examined the effects on zinc homeostasis. We found that ZIP5 is not essential for growth and viability but total knockout of ZIP5 led to increased zinc in the liver in mice fed a zinc-adequate (ZnA) diet but impaired accumulation of pancreatic zinc in mice fed a zinc-excess (ZnE) diet. Loss-of-function of enterocyte ZIP5, in contrast, led to increased pancreatic zinc in mice fed a ZnA diet and increased abundance of intestinal Zip4 mRNA. Finally, loss-of-function of acinar cell ZIP5 modestly reduced pancreatic zinc in mice fed a ZnA diet but did not impair zinc uptake as measured by the rapid accumulation of 67zinc. Retention of pancreatic 67zinc was impaired in these mice but the absence of pancreatic ZIP5 sensitized them to zinc-induced pancreatitis and exacerbated the formation of large cytoplasmic vacuoles containing secretory protein in acinar cells. Conclusions These studies demonstrate that ZIP5 participates in the control of zinc excretion in mice. Specifically, they reveal a paramount function of intestinal ZIP5 in zinc excretion but suggest a role for pancreatic ZIP5 in zinc accumulation/retention in acinar cells. ZIP5 functions in acinar cells to protect against zinc-induced acute pancreatitis and attenuate the process of zymophagy. This suggests that it may play a role in autophagy.